HUBUNGAN INDEKS MASA TUBUH TERHADAP USIA MENARCHE PADA SISWI SMP ST KLUS KUWU RUTENG, MANGGARAI - odilia esem (STIKes CHMK, 2023)
The puberty period that occurs in a young girl is marked by menstruation. The first menstruation (menarche) is a very important event in a woman's reproductive life cycle. The nutritional status of young women greatly influences the occurrence of menarche both from the age of menarche, complaints during menarche and the length of menarche. This study aims to determine the relationship between body mass index and the age of menarche. This cross-sectional study was conducted on female students at St. Klaus Kuwu Middle School, with a population of 21 respondents. The sampling technique in this study was total sampling. Statistical analysis using the Chi square test. The results of the study showed that most of those with a body mass index were in the normal category, namely as many as 11 people (52.4%) and most of those who experienced menarche were in the normal category, namely as many as 20 people (95.2%). Chi square analysis for the relationship between body mass index (BMI) and menarche age obtained a value of 0.000. The significant value is lower than the significant level of 0.05. So it is stated that there is a relationship between body mass index and the age of menarche at St. Klaus Kuwu Middle School. Nutritional intake obtained by a young woman either adequately or excessively affects the body's growth hormone, in particular can accelerate the maturity of reproductive hormones so that early menarche or menarche can occur on time, and vice versa if a young woman gets insufficient nutritional intake, it will affects the decline in reproductive function which results in menarche at an inappropriate age. Keywords: body mass index, menarche age, young women.